Method for manufacturing vehicle structure and method for treating molded body for vehicle
The method of plasma treatment combined with a treatment liquid and high humidity storage enhances adhesion between resin surfaces and transparent substrates, addressing the issue of insufficient bond strength in molded bodies, and improving durability and bond strength without the need for primers.
Patent Information
- Application Number
- JP2020559099
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-03
- Filing Date
- 2019-11-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2039-11-27
AI Technical Summary
The adhesion between molded bodies with a resin surface and transparent substrates bonded using adhesives is insufficient, leading to potential deterioration of the bond when plasma treatment is used for surface modification.
A manufacturing method involving plasma treatment of the resin surface, followed by application of a treatment liquid containing water or a hydrophilic organic solvent, and storing the molded body in a high humidity environment to enhance adhesion, which includes steps of plasma treatment, molecule adsorption, and adhesion with an adhesive in a high humidity condition.
The method significantly improves the adhesion between the molded body and the adhesive, preventing deterioration and enhancing the bond strength, even without the use of primers, by increasing the number of hydrophilic functional groups and accelerating adhesive curing.
Smart Images

Figure 0007600686000011 
Figure 0007600686000012 
Figure 0007600686000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for manufacturing a vehicle structure and a method for treating a molded article for a vehicle. [Background technology]
[0002] Many resin parts, or parts having resin at least on their surfaces, are known as parts used in vehicles such as automobiles. Some of these parts are bonded to a transparent substrate such as glass with an adhesive, and examples include molded articles such as resin brackets for mounting on-board equipment on the inner surface of a windshield. Such molded articles are often bonded to a transparent substrate with an adhesive.
[0003] Incidentally, it is generally known that in order to improve the adhesiveness of the resin surface of the molded article, the surface of the molded article is modified by irradiating the molded article with plasma or the like (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2016-56363 Summary of the Invention [Problem to be solved by the invention]
[0005] However, when bonding a molded body having a resin surface as described above to a transparent substrate for a vehicle via an adhesive, the adhesion between the molded body and the adhesive may not be sufficient simply by treating the resin surface of the molded body with plasma, etc. Therefore, in producing a structure in which a molded body and a transparent substrate for a vehicle are bonded together with an adhesive, a method for improving the adhesion between the molded body and the adhesive is desired.
[0006] In view of the above, one aspect of the present invention aims to provide a manufacturing method for a structure formed by bonding a transparent substrate and a molded body having a resin surface with an adhesive, which can improve the adhesion between the molded body having a resin surface and the adhesive. [Means for solving the problem]
[0007] In order to solve the above-mentioned problems, one aspect of the present invention is a method for manufacturing a molded article having a resin surface, comprising: a plasma treatment step of performing plasma treatment on the molded article; and applying water to the surface of the molded article after the plasma treatment step. of and an adhesion step of adhering the molded body after the molecular adsorption step to a transparent substrate for a vehicle with an adhesive to obtain a vehicle structure, wherein the molecular adsorption step is carried out by storing the molded body in a high-humidity environment, and the storage in the high-humidity environment is storage in an environment with a relative humidity of 80% RH or higher. [Effects of the Invention]
[0008] According to one aspect of the present invention, a manufacturing method can be provided for producing a structure in which a transparent substrate and a molded body having a resin surface are bonded together with an adhesive, which can improve the adhesion between the molded body having a resin surface and the adhesive. [Brief explanation of the drawings]
[0009] [Figure 1] 1 is a plan view of a vehicle structure according to an embodiment of the present invention; [Figure 2] FIG. 2 is a partial cross-sectional view taken along line II in FIG. DETAILED DESCRIPTION OF THE INVENTION
[0010] Hereinafter, embodiments for carrying out the present invention will be described, but the present invention is not limited to the following embodiments.
[0011] <Plasma treatment step> The plasma treatment step is a step of irradiating the surface of a molded article having a resin surface with plasma. The plasma generation means used in this step is not particularly limited and may be a high-frequency plasma generator or a low-frequency plasma generator. Furthermore, the plasma treatment in the plasma treatment step may be a treatment that can generate corona, so-called corona treatment. Furthermore, it may be a treatment that utilizes plasma generated by irradiation with a laser, microwaves, or the like.
[0012] The molded article having a resin surface to be treated in this embodiment may be any article containing a resin at least on the surface. That is, the molded article having a resin surface may be, for example, a resin molded article in which the entire molded article is mainly formed from resin, or a molded article made of a material other than resin, the surface of which is partially or entirely coated with resin. In this specification, the molded article having a resin surface may be referred to as a "resin molded article" or simply as a "molded article."
[0013] The resin material used for the molded article having a resin surface is not particularly limited, but examples include polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), polyolefins such as polyethylene (PE) and polypropylene (PP), polycarbonate (PC), polyamides (PA) such as nylon 6 and nylon 6,6, high-heat-resistant polyamides based on terephthalic acid or isophthalic acid (PA6T, PA6I, PA6T / 6I, etc.), polyimide (PI), polyetherimide (PEI), acrylonitrile-butadiene-styrene (ABS), polyacetal (POM), polyvinyl chloride (PVC), and epoxy (EP). These resin materials may be used as homopolymers or as copolymers combining one or more of the above. Furthermore, particularly when the molded article is made of resin, the resin material is preferably a polymer alloy combining one or more of the above, such as a polymer alloy of polybutylene terephthalate and styrene-acrylonitrile.
[0014] The resin material may be a resin reinforced with a filler such as fiber or inorganic particles. Examples of the reinforcing fiber include glass fiber and carbon fiber. Examples of the fiber-reinforced resin include glass fiber-reinforced polybutylene terephthalate and polyetherimide. When the resin contains reinforcing fiber, the fiber content can be about 5 to 70% by mass, preferably about 30 to 50% by mass, based on the total mass of the resin.
[0015] When the molded article having a resin surface is a resin molded article, the molding method is not limited, and the above-mentioned resin material may be molded by a method such as injection molding, casting, extrusion, blow molding, etc. Also, it may be insert molded using an insert material made of a material other than resin (metal, etc.).
[0016] Furthermore, when the molded article having a resin surface is a molded article made of a material other than resin, the surface of which is partially or entirely coated with resin, it may be, for example, an electrodeposition-coated article obtained by electrodeposition-coating a substrate made of metal or the like with an electrodeposition paint containing a resin. The electrodeposition-coated article is formed by passing an electric current through an electrolytic bath to deposit resin paint particles on the surface of the part, and then heating and curing the resulting film in a curing oven. When the resin surface is formed by electrodeposition coating, the electrodeposition paint is preferably a cationic electrodeposition paint. Furthermore, the resin contained in the electrodeposition paint may be a thermosetting resin such as an epoxy resin, and preferably contains an epoxy resin modified with an amine, ammonium, or the like. Meanwhile, the substrate may be a molded article made of metal, such as steel or aluminum, particularly a plate-shaped molded article. An example of an electrodeposition-coated article is a cationic electrodeposition-coated steel plate manufactured by Aoki Electric Industrial Co., Ltd. (using Elecron HG-305E Black manufactured by Kansai Paint Co., Ltd. as the electrodeposition paint).
[0017] The resin surface can also be formed by applying a solution or dispersion containing a resin, or a molten resin, or the like, onto the substrate, or by depositing a pre-formed sheet-like resin layer, or by electroless plating, or the like.
[0018] In the molded article having a resin surface, it is sufficient that at least a part of the substrate surface is covered with a resin layer. In addition, in the molded article having a resin surface, it is sufficient that at least a part of the surface (adhesion surface) to be bonded to the later-described transparent substrate for a vehicle is covered with a resin layer, and it is preferable that the entire adhesion surface is covered with a resin layer.
[0019] In one embodiment of the present invention, a molded article having a resin surface as described above can first be chemically surface-modified by a plasma treatment step. The plasma treatment step can introduce or form hydrophilic functional groups, such as hydroxyl groups, carbonyl groups, and carboxyl groups, on the resin surface, thereby increasing the number of hydrophilic functional groups per unit area. This increases the number of sites where the hydrophilic functional groups on the surface can interact with the adhesive components through chemical bonding or intermolecular forces when the molded article is bonded to an adherend, such as a transparent substrate, using the resin surface as the bonding surface and an adhesive. This strengthens the bond (interfacial bond) between the molded article and the adhesive.
[0020] On the other hand, increasing the number of hydrophilic functional groups per unit area means that the number of sites on which hydrophilic molecules can be adsorbed can be increased, and the amount (density) of hydrophilic molecules that can stably exist on the resin surface of the molded article can be increased. According to one aspect of the present invention, it has been discovered that by performing molecular adsorption on such sites before applying the adhesive, it is possible to enhance the effect of accelerating the curing of the adhesive at the interface between the molded article and the adhesive, which will be described later.
[0021] The conditions for plasma irradiation can be adjusted as appropriate depending on the types of resin and adhesive used in the molded body, the intended use of the molded body, and the location in the vehicle where it is used. While it is difficult to generalize because it depends on the plasma generator and the constituent materials of the molded body, for example, the frequency of the voltage applied to the power supply of the plasma generating means is 50 Hz to 2.45 GHz, preferably 50 Hz to 25 kHz, and the irradiation distance (the distance between the electrode and the surface of the molded body) is 50 mm or less, preferably 10 mm to 30 mm. The lower limit of the distance between the opposing nozzle and the workpiece (molded body) is not particularly limited, but is, for example, 0.5 mm or more. The output power density is 15 W / cm 2 or more, preferably 20 W / cm 2 The irradiation time is determined by the nozzle movement speed. The nozzle movement speed can be set to 0.01 m / min to 50 m / min, preferably 2.5 m / min to 10 m / min, and more preferably 2.5 m / min to 4 m / min. If the irradiation distance is 10 mm and the nozzle movement speed is in the range of 2.5 m / min to 4 m / min, even plastics that are difficult to modify can be modified.
[0022] When performing the plasma treatment step, if the surface temperature of the molded body having a resin surface is increased by, for example, heating the molded body with a heater before plasma irradiation, the adhesion between the molded body and the adhesive in the structure obtained through the subsequent steps can be further improved. Also, the hot water durability of the resulting vehicle structure (durability when the molded body and the transparent substrate are bonded with an adhesive and then immersed in hot water for a predetermined time) can be improved.
[0023] The surface temperature of the molded body before plasma irradiation can be raised to a temperature above room temperature (15°C to 25°C), for example, 60°C or higher, preferably 80°C or higher, more preferably 100°C or higher, even more preferably 120°C or higher, and even more preferably 140°C or higher.
[0024] In the plasma treatment step, in addition to the above-mentioned chemical modification, physical surface modification such as forming fine irregularities on the resin surface of the molded body is also possible depending on conditions such as the strength and duration of the irradiated plasma.
[0025] Regarding the storage temperature of the molded body before the plasma treatment step, when storing a highly hygroscopic material, such as polyamide with a saturated water absorption rate of 1% or more, it is desirable that the storage temperature be 25°C or lower.
[0026] <Molecular adsorption step> In the molecular adsorption step, a treatment liquid is supplied to the surface of the molded body after the plasma treatment step, so that molecules of the treatment liquid can be adsorbed onto the resin surface of the molded body. The treatment liquid may contain at least one of water and a hydrophilic organic solvent. That is, the treatment liquid may be water or one or more hydrophilic organic solvents, or a mixture of water and one or more hydrophilic organic solvents.
[0027] In this specification, "adsorbing molecules onto the surface of a molded article" refers to binding molecules to functional groups present on the resin surface of the molded article by intermolecular forces, and may also refer to so-called monolayer adsorption of molecules onto the resin surface of the molded article. Furthermore, "surface-adsorbed molecules" or "adsorbed molecules" refer to molecules directly bonded to functional groups present on the resin surface of the molded article. In contrast, molecules present on the resin surface of a molded article that are not directly bonded to functional groups present on the resin surface of the molded article are sometimes referred to as "condensed molecules."
[0028] As described above, hydrophilic functional groups are introduced or formed on the resin surface of the molded body by the plasma treatment step, and these hydrophilic functional groups are easily bonded to water molecules and hydrophilic molecules. Therefore, by supplying a treatment liquid containing at least one of water and a hydrophilic organic solvent to the surface of the molded body, molecules of the water or hydrophilic organic solvent can be easily adsorbed onto the resin surface of the molded body. In other words, water molecules and / or molecules of the hydrophilic organic solvent can be directly bonded to the hydrophilic functional groups present on the resin surface of the molded body through hydrogen bonding, van der Waals forces, etc. Such direct bonding allows the treatment liquid molecules to be stably present on the resin surface of the molded body.
[0029] The manufacturing method according to this embodiment further includes a step of adhering an adherend such as a transparent substrate using an adhesive after the molecular adsorption step (the adhesion step described below). As a result of extensive research, it has been found that the presence of treatment liquid molecules adsorbed on the surface of the molded body as described above reliably improves the adhesion between the molded body and the adhesive. This in turn improves the adhesive strength between the molded body and an adherend such as a transparent substrate. Although the detailed mechanism behind this has not yet been clarified, it is presumed that the adsorbed molecules have the effect of increasing intermolecular forces or promoting curing near the interface.
[0030] The former effect can be explained by the fact that the presence of adsorbed molecules improves the wettability between the adhesive and the resin surface, making it easier for intermolecular forces such as electrostatic interactions and van der Waals forces to act.
[0031] The latter effect is thought to be as follows: Generally, adhesives contain additives such as plasticizers in addition to adhesive components. If the adhesive cures slowly, these additive components may migrate to the interface and reduce the adhesive strength between the molded body and the adherend. In contrast, the treatment liquid molecules present on the resin surface of the molded body accelerate the curing of the adhesive, preventing the additive components from migrating to the vicinity of the interface. This is thought to reduce the effect of the additive components in the adhesive on the adhesion at the interface between the molded body and the adhesive.
[0032] As described above, the treatment liquid contains at least one of water and a hydrophilic organic solvent. The total amount of water and hydrophilic organic solvent in the treatment liquid is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. The treatment liquid is preferably water, a hydrophilic organic solvent, or a mixture thereof.
[0033] The treatment liquid preferably contains water because it is low cost, safe, and easy to operate. As can be seen from the fact that distilled water is used as the treatment liquid in the examples, no special additives are required. The amount of water in the treatment liquid is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, based on 100% by mass of the treatment liquid. It is even more preferable that the treatment liquid is water.
[0034] When the treatment liquid contains a hydrophilic organic solvent, the hydrophilic organic solvent contained therein is not particularly limited as long as it is an organic solvent that has affinity with the hydrophilic groups present on the resin surface of the molded body and does not denature the resin material used in the molded body.
[0035] Examples of hydrophilic organic solvents used in the treatment solution include alcohols such as methanol, ethanol, 2-propanol (isopropyl alcohol), and 1-propanol; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; esters such as butyl acetate, ethyl acetate, and glycol ester; aliphatic or alicyclic hydrocarbons such as n-hexane and cyclohexane; and ethers such as diethyl ether and glycol ether. These organic solvents can be used alone or in combination of two or more. Among these organic solvents, it is preferable to use one or more of methanol, ethanol, acetone, methyl ethyl ketone, butyl acetate, and ethyl acetate.
[0036] Some organic solvents inevitably contain trace amounts of water. This unavoidable water content may be water that cannot be removed during the production process of the organic solvent, or water that is mixed into the treatment solution despite not being actively added during the preparation process. For example, organic solvents generally contain unavoidable amounts of water in amounts of 5% by mass or less, 1% by mass or less, 0.5% by mass or less, 0.2% by mass or less, or 0.1% by mass or less, based on 100% by mass of the organic solvent. The present invention is effective even for organic solvents that contain such trace amounts of water and have reduced purity.
[0037] Furthermore, there is a possibility that such inevitably contained water molecules can directly bond to the functional groups on the surface of the molded body. Therefore, in the bonding step described below, especially when a moisture-curing adhesive is used, the water molecules inevitably contained in the organic solvent can also promote the curing of the adhesive, thereby improving the adhesive strength with the adhesive.
[0038] Therefore, when the treatment liquid contains an organic solvent or consists of an organic solvent, the content of unavoidable water contained in the organic solvent before preparation of the treatment liquid can be 0.001% by mass or more, 0.1% by mass or more, 0.2% by mass or more, 0.4% by mass or more, 0.5% by mass or more, 1% by mass or more, or 5% by mass or more, relative to 100% by mass of the treatment liquid.
[0039] When the treatment liquid contains water together with a hydrophilic organic solvent, if the hydrophilic organic solvent is volatile, after the treatment liquid is supplied to the surface of the resin molded body, the organic solvent volatilizes first, and the water molecules are more likely to adsorb to the resin surface of the molded body. That is, the water molecules are more likely to bond with functional groups present on the resin surface of the molded body. In this way, when the adsorbed molecules are mainly water molecules, particularly when a moisture-curing adhesive is used in the bonding step, the curing of the adhesive is promoted, making it possible to prevent the migration of additive components such as plasticizers in the adhesive.
[0040] The treatment liquid may contain any additives, such as isocyanate, silane coupling agent, and preservative.
[0041] The treatment liquid may be substantially free of organic compounds having a sulfo group. In this specification, "substantially free of a predetermined component" refers to not adding the predetermined component as a constituent when preparing the treatment liquid. The content of organic compounds having a sulfo group in the treatment liquid used in this embodiment may be, for example, less than 0.5% by mass, specifically 0.1% by mass or less, more specifically 0.01% by mass or less, and even more specifically less than 0.001% by mass.
[0042] The treatment liquid may be substantially free of strong acid components, including organic compounds having a sulfo group, and may also be substantially free of acid components. Examples of acid components include organic compounds having a sulfo group, as well as inorganic acids such as hydrochloric acid, hydrofluoric acid, hydrobromic acid, hydroiodic acid, nitric acid, and sulfuric acid, and organic acids (excluding alcohols) such as carboxylic acids and thiols, and derivatives thereof.
[0043] By making the treatment solution substantially free of organic compounds having sulfo groups and further by making it substantially free of strong acid components, corrosion of surrounding metals can be reduced. In particular, when the molded body to be treated contains metal therein, corrosion of the metal contained in the molded body can be effectively prevented. Furthermore, since many metal-containing parts are used in vehicles such as automobiles, substantially eliminating the use of acid components in the manufacture of vehicle structures can reduce adverse effects on metal parts inside the vehicle. Furthermore, by making the treatment solution substantially free of acid components, a more inexpensive process can be realized.
[0044] According to the manufacturing method of this embodiment, functional groups can be introduced or formed on the resin surface of the molded body through the plasma treatment step, and treatment liquid molecules can be adsorbed through the molecular adsorption step. This strengthens the bond between the subsequently applied adhesive and the molded body surface, promotes curing of the adhesive at the interface with the molded body and its vicinity, and prevents a decrease in adhesion due to migration of additive components. In this way, the two steps of plasma treatment and molecular adsorption of this embodiment can improve the adhesion between the molded body having a resin surface and the adhesive. Therefore, according to this embodiment, a structure can be obtained in which the molded body and the adherend are bonded with high adhesion directly via the adhesive, without applying a primer or the like to the resin surface of the molded body. Furthermore, when a primer is used for adhesion, the adhesion between the molded body and the primer can also be improved.
[0045] Even in an untreated state, the surface of a molded body may contain a certain amount of adsorbed molecules (especially water molecules) that can act on the adhesive when the adhesive is applied. However, the amount is generally small, making it difficult to achieve the excellent adhesion achieved by the embodiment of the present invention. Furthermore, when plasma treatment is performed on the resin surface of a molded body, the adsorbed molecules may disappear depending on the treatment conditions. For example, if plasma treatment is performed under strong conditions, such as long-term, high-power irradiation, the adsorbed molecules may dissipate. Even in such cases, in this embodiment, molecules of the treatment solution are adsorbed onto the resin surface of the molded body after plasma treatment, thereby improving the adhesion between the molded body and the adhesive regardless of the plasma treatment conditions.
[0046] More specifically, the supply of the treatment liquid to the surface of the molded body in the molecular adsorption step can be carried out as follows.
[0047] A first form of the molecular adsorption step involves contacting the compact with a treatment liquid using a tool or the like. This contact with the treatment liquid can involve leaving the compact in contact with the treatment liquid and moving the treatment liquid relative to the compact while it is in contact with the compact. For example, the compact can be immersed in the treatment liquid contained in a container or the like. Here, immersion can involve immersing the compact in the treatment liquid for a predetermined time and then removing it, pouring the treatment liquid over the surface of the compact, or rinsing the compact with the treatment liquid. Immersing compacts in the treatment liquid not only allows for batch processing, i.e., immersing multiple compacts simultaneously, but also facilitates automation, as there is no need to change the immersion treatment configuration (job change) for each different compact.
[0048] The treatment liquid can also be supplied by spraying the treatment liquid onto the surface of the molded body. Spraying the treatment liquid includes splashing droplets of the treatment liquid, spraying with a sprayer, or spraying with heated steam. The treatment liquid can also be applied by coating. For example, the treatment liquid can be applied by soaking a cloth or cotton or the like in the treatment liquid and stroking the surface of the molded body with the cloth or cotton, or by using a brush. On the other hand, if the treatment liquid is soaked in a cloth or cotton and then stroking the surface of the molded body with the cloth or cotton, there is a concern that fibers or compounds contained in the cloth or cotton may remain on the adhesive surface during application and inhibit adhesion. Static electricity may also be generated, which may cause foreign matter to adhere to the applied surface. Therefore, it is preferable to immerse the molded body in the treatment liquid contained in a container or the like, or to spray the treatment liquid onto the surface of the molded body. If the treatment liquid is supplied by coating, it is preferable to do so without applying pressure to the surface of the molded body, or to keep the pressure on the surface of the molded body to approximately 0.2 kPa or less. This reduces the possibility of fibers or compounds remaining on the adhesive surface.
[0049] A second form of the molecular adsorption step involves forming a space in which the treatment liquid (molecules of the treatment liquid) can exist in a gaseous state, and placing the molded body so that the resin surface is exposed within the space. For example, a space is formed in which the vapor pressure of at least one of the water and hydrophilic organic solvent that make up the treatment liquid is elevated, and the molded body is stored within the space for a predetermined period of time. This allows the treatment liquid molecules in a gaseous state to be adsorbed onto the resin surface of the molded body. It is preferable to store the molded body for at least a period of time sufficient to reach adsorption equilibrium.
[0050] When the treatment liquid is water, the molded body can be stored in a high-humidity environment. Here, a high-humidity environment may be an environment with a humidity higher than normal humidity (relative humidity 45 to 85% RH). Furthermore, molecular adsorption due to storage in a high-humidity environment can be prevented by storage in an environment with a relative humidity of 60% RH or higher, preferably 80% RH or higher, and more preferably 90% RH or higher. Note that when storing a highly hygroscopic material, such as polyamide with a saturated water absorption rate of 1% or higher, in a high-humidity environment of 60% RH or higher, the storage temperature is preferably 30°C or lower.
[0051] In both the first and second forms of the molecular adsorption step, it is preferable that, after the step, the treatment liquid molecules are adsorbed to at least the functional groups on the surface of the molded article in an amount that achieves adsorption equilibrium.
[0052] Furthermore, before the plasma treatment step, the surface of the molded body can be cleaned by a known method. That is, the manufacturing method according to this embodiment may have a cleaning step before the plasma treatment step. The cleaning step allows fine dust or dirt on the surface of the molded body to be physically or chemically removed in advance. That is, specific examples of cleaning include removing dust or dirt present on the surface of the molded body by mechanical force, dissolving the dust or dirt in a solvent, decomposing the dust or dirt with a solvent, or a combination thereof. Of the above, it is preferable to include the application of mechanical force, as this allows for efficient cleaning.
[0053] If dust or dirt on the surface of the molded article can be sufficiently removed in advance, more hydrophilic functional groups can be introduced to the surface of the molded article in the subsequent plasma treatment, and the hydrophilic functional groups can form more stable bonds with the surface of the molded article. This eliminates the need for excessively high plasma treatment conditions and reduces the possibility of damaging the resin surface due to excessive surface treatment.
[0054] The cleaning method is not particularly limited, and examples include wiping, polishing, washing, etc. In wiping, the surface of the molded body is wiped with a wiping tool, at least in the area where plasma treatment is to be performed. In this case, the wiping material of the wiping tool may be impregnated with a solvent. The wiping tool may be, for example, one equipped with a fibrous or porous wiping material that can absorb and retain the solvent. The wiping material may be a sheet-like material such as cloth or nonwoven fabric, or a bulk material such as a sponge. The solvent is preferably one that can disperse or dissolve dust or dirt that may be present on the molded body surface, and is preferably volatile.
[0055] In wiping, dust and dirt can be removed from the surface of the molded body by mechanical force while decomposing the dirt with a solvent or dissolving the dirt in the solvent. Wiping can be performed without applying pressure to the surface of the molded body, or by applying a pressure of about 0.2 kPa to 60 kPa to the surface of the molded body. Wiping with pressure can reliably remove dirt from the surface of the molded body.
[0056] When cleaning by polishing, a known surface polishing method using an abrasive and a polishing tool can be used. By polishing, a small amount of material on the surface of the resin molded body is scraped off, so dirt on the resin surface can be sufficiently removed. As the abrasive, for example, mineral particles or a dispersion of mineral particles can be used, but particles of a substance that has sublimation properties, i.e., that sublimates at room temperature and normal pressure, such as carbon dioxide, can also be used. By using sublimation particles, it is not necessary to remove the abrasive after the polishing process is completed.
[0057] The cleaning can be performed using a known cleaning method for resin molded bodies. For example, the molded body can be immersed in a cleaning liquid such as a solvent, left to stand for a predetermined time, and then removed. Alternatively, after immersing the molded body in the cleaning liquid, the cleaning liquid may be moved relative to the surface of the molded body by flowing it. Alternatively, for example, the cleaning liquid may be poured over the molded body. The solvent is preferably volatile and capable of dispersing or dissolving dust or dirt that may be present on the surface of the molded body.
[0058] <Excess molecule removal step> After the molecular adsorption step, depending on the method of applying the treatment liquid, excess treatment liquid molecules may be present on the surface of the molded article. In such cases, it may be difficult for the adhesive molecules and the molecules on the resin surface to approach each other closely enough to interact, resulting in a failure to adhere. Therefore, it is important to balance the amount of hydrophilic functional groups on the resin surface of the molded article with the amount of treatment liquid molecules.
[0059] Therefore, the manufacturing method according to this embodiment may include an excess molecule removal step for removing excess treatment liquid molecules after the molecular adsorption step. In such an excess molecule removal step, at least a portion of the condensed molecules of the treatment liquid can be removed. Furthermore, by removing the condensed molecules of the treatment liquid, the treatment liquid can be made to exist mainly as adsorbed molecules on the surface of the molded body. Thus, in the excess molecule removal step, it is preferable that the condensed molecules are removed, but the adsorbed molecules are not. Therefore, the excess molecule removal step does not include forced removal of treatment liquid molecules by drying, such as by applying excessively high heat or blowing gas.
[0060] As a specific method for the excess molecule removing step, the molded body after the molecular adsorption step may be left for a predetermined time to allow the treatment liquid to evaporate naturally, or the visible treatment liquid may be absorbed into cloth, cotton, etc. In the excess molecule removing step, it is preferable to remove the treatment liquid at least until the treatment liquid can no longer be visually confirmed on the resin surface of the molded body.
[0061] The excess molecule removal step can remove excess treatment molecules and optimize the state of the treatment solution molecules on the surface of the molded article. That is, the amount (density) of hydrophilic functional groups present on the surface of the molded article can be balanced with the amount (density) of treatment solution molecules. This makes it possible to balance the interfacial bonding between the surface of the molded article and the adhesive and the cohesion within the adhesive when the adhesive is applied.
[0062] Regardless of whether or not there is an excess molecule removal step, the amount of treatment liquid molecules adsorbed on the surface per unit area immediately before the adhesion step described next is 13 to 15 H2O molecules / nm 2 It is preferable that the density of the adsorbed water molecules is 1 / 2.
[0063] <Adhesion step> After the molecular adsorption step, and optionally after the above-mentioned excess molecule removal step, the molded body having a resin surface can be adhered to a transparent substrate for a vehicle with an adhesive.
[0064] In the bonding step, an adhesive can be applied to the resin surface of the molded body that has been subjected to plasma treatment and has adsorbed treatment liquid molecules, and then the vehicle transparent substrate can be placed on top of it. Alternatively, the adhesive can be applied to the vehicle transparent substrate, and the resin surface of the molded body can be placed on top of the adhesive. In either case, a primer specifically for transparent substrates can be applied to the vehicle transparent substrate side.
[0065] The adhesive used in the bonding step is preferably a one-component or two-component moisture-curing adhesive, and more preferably a urethane-based adhesive, a modified silicone-based adhesive, or the like. When a moisture-curing adhesive is used, the curing of the adhesive can be promoted by using a treatment liquid containing water. In addition to one-component or two-component moisture-curing adhesives, photo-curing adhesives and thermo-curing adhesives can also be used. When a photo-curing adhesive or thermo-curing adhesive is used, it is presumed that the adhesiveness is improved by the action of adsorbed molecules, which improve the wettability between the resin molded body surface and the adhesive after the plasma treatment step.
[0066] In the bonding step, after bonding with an adhesive, the structure obtained by bonding the molded body having a resin surface to the transparent substrate via the adhesive may be stored, i.e., cured, in a predetermined environment.
[0067] The optimum conditions for curing vary depending on the materials of the molded body and adhesive, the conditions of the plasma treatment step and the molecular adsorption step, etc., but the curing temperature is preferably 5 to 35°C. The humidity during curing can be about 20 to 80% RH. Note that the structure can also be cured at a high temperature, for example, at a temperature above room temperature, by heating the structure, etc. This can further improve the adhesion between the adhesive and the molded body.
[0068] The vehicle transparent substrate used in this embodiment can be vehicle glass, such as a windshield, rear window, or side window. The vehicle glass may be formed from a glass plate such as soda lime silicate glass, aluminosilicate glass, borate glass, lithium aluminosilicate glass, or borosilicate glass. The glass plate may be untempered, or may have been subjected to air-cooled or chemically tempered treatment. Untempered glass is formed by shaping molten glass into a plate and slowly cooling it. Tempered glass is formed by forming a compressive stress layer on the surface of untempered glass. When the tempered glass is air-cooled tempered glass, the glass surface may be tempered by rapidly cooling a uniformly heated glass plate from a temperature near its softening point, thereby generating compressive stress on the glass surface due to the temperature difference between the glass surface and the interior of the glass. On the other hand, when the tempered glass is chemically tempered glass, the glass surface may be tempered by generating compressive stress on the glass surface using an ion exchange method or the like. The vehicle glass may be a glass plate that absorbs ultraviolet or infrared rays, and is preferably transparent, but may also be colored to the extent that transparency is not impaired. The vehicle glass may also be organic glass. Examples of organic glass include transparent resins such as polycarbonate.
[0069] When the vehicle transparent substrate is a vehicle glass, gravity forming, press forming, or the like is used to bend the glass plate used. The forming method of the glass plate is not particularly limited, but for example, glass formed by a float method or the like is preferred. In addition, the vehicle glass can be a laminated glass including a plurality of the above-mentioned glass plates. An interlayer film such as ethylene vinyl acetal or polyvinyl butyral can be provided between the glass plates constituting the laminated glass.
[0070] The shape of the vehicle transparent substrate is not limited to a rectangular shape, and the vehicle transparent substrate may be processed to have various shapes. The vehicle transparent substrate may also be curved, and its curvature is not particularly limited. However, the vehicle transparent substrate has a shape and curvature that allow a molded body having a resin surface to be bonded to the surface of the vehicle transparent substrate, and that allow sufficient plasma irradiation to improve adhesion to the molded body to be performed.
[0071] The bonding step can provide a vehicle structure in which the molded body and the transparent substrate are bonded together with an adhesive. Specific examples of vehicle structures include a vehicle window glass, such as a windshield, to which vehicle components such as resin brackets and resin temporary fixing pins for mounting on-board equipment (on-board cameras, on-board sensors, etc.) are bonded. Furthermore, the vehicle structure can also include a structure in which vehicle components such as resin door sliders and resin door holders are bonded to side glass. It is preferable that the vehicle molded body bonded to the transparent substrate to form the structure in this way has at least a plate-like, flat portion to be bonded.
[0072] FIG. 1 shows a plan view of an example vehicle structure 1 in which a resin bracket 20 is bonded to a glass 10, as viewed from the interior side of the vehicle. The structure in FIG. 1 is formed by bonding a resin bracket 20 for in-vehicle equipment to the interior side of the windshield 10. The bracket 20 is configured to support at least an in-vehicle camera. FIG. 2 shows a partial cross-section taken along line II in FIG. 1. As shown in FIG. 2, an adhesive layer 30 is disposed between the windshield 10 and the bracket 20. Note that the resin bracket 20 for in-vehicle equipment is not limited to an in-vehicle camera. It may be any device that can be supported by the resin bracket 20 bonded to the glass 10, such as a rain sensor, an infrared sensor, or a millimeter-wave radar.
[0073] As shown in FIGS. 1 and 2 , a shielding layer 15 may be provided on the periphery of the interior surface of the glass 10. When the glass 10 is laminated glass, the shielding layer 15 may be provided on both the glass sheet located on the exterior side of the vehicle and the glass sheet located on the interior side of the vehicle, or on only one of them. The shielding layer 15 functions to protect urethane sealants and other materials that adhere and hold the vehicle transparent substrate to the vehicle body from deterioration due to ultraviolet rays. The shielding layer 15 is formed, for example, by applying and firing a ceramic color paste containing a fusible glass frit containing a black pigment. The thickness of the shielding layer 15 is preferably 3 μm to 15 μm. The width of the shielding layer 15 is not particularly limited, but is preferably 20 mm to 300 mm. In the illustrated example, the bracket 20 is bonded to the shielding layer 15 provided on the interior surface of the glass 10. However, the bracket 20 may also be bonded directly to the interior surface of the glass 10. When viewed from outside the vehicle, it is preferable that bracket 20 be adhered in a position that is hidden by shielding layer 15. When bracket 20 is adhered in a position that is hidden by shielding layer 15, not only does it become difficult for bracket 20 and adhesive layer 30 to be seen from outside the vehicle, but it also makes it possible to suppress deterioration of adhesive layer 30 due to ultraviolet rays.
[0074] In the vehicle structure obtained by this embodiment, the adhesion between the molded body having a resin surface and the adhesive is enhanced even without the use of a primer, so that even when an external force is applied to the vehicle structure, peeling at the interface between the molded body and the adhesive is unlikely to occur. [Example]
[0075] Hereinafter, the embodiments of the present invention will be described in more detail based on examples.
[0076] <Resin materials> The materials of the molded bodies used in the examples are as follows. Resin PBT1: Glass fiber reinforced polybutylene terephthalate (manufactured by Polyplastics Co., Ltd., "DURANEX (registered trademark) 733LD") Resin PBT2: Glass fiber reinforced polybutylene terephthalate (manufactured by BASF Japan Ltd., "ULTRADUR (registered trademark) B4300G6") Resin PBT3: Glass fiber reinforced polybutylene terephthalate (manufactured by Mitsubishi Engineering Plastics Corporation, "NovaDuran (registered trademark) 5010G30J") Resin PA: Glass fiber reinforced polyamide (PA6T / 6I) (Ms Chemie Japan Co., Ltd., "Grivory (registered trademark) HTV-3H1 9025") Resin PEI: Polyetherimide (SABIC, "Ultem (registered trademark) 1000")
[0077] <Adhesion evaluation (knife cut test)> The adhesive strength between the test piece and the molded body was evaluated by a manual peel test using a knife cut. The manual peel test was performed by making a cut of a certain length with a cutter knife between the adhesive layer of the test piece and the plate-shaped molded body (at the interface between the adhesive and the molded body), and then pulling the adhesive layer from the cut to peel it off from the molded body. After applying a certain force, the cutter knife was inserted deeper between the adhesive layer and the plate-shaped molded body to make a cut, and the adhesive layer was repeatedly peeled off to check the peeling state of the adhesive.
[0078] After the manual peel test was completed, the state of failure on the surface of the molded article was visually observed, and the percentage of the area where the adhesive had undergone cohesive failure was recorded as the cohesive failure rate (CF rate, unit: %). A CF rate of 0% means that the adhesive had not undergone cohesive failure at all and interfacial peeling had occurred, and a CF rate of 100% means that cohesive failure had occurred over the entire surface where the adhesive was applied. The higher the CF rate, the greater the percentage of cohesive failure that had occurred in the adhesive, and the better the adhesion between the molded article and the adhesive was evaluated to be.
[0079] [1. Molecular adsorption by the first method (immersion, etc.)] (Example 1-1) A plate-shaped molded body (25 mm × 150 mm × 5 mm) made of resin PBT1 was prepared as the molded body. First, the surface of the plate-shaped molded body was cleaned by wiping it with hexane (Sigma-Aldrich Japan, LLC, special grade reagent) and a nonwoven wiper (Asahi Kasei Corporation, Bemcot (registered trademark)) soaked in hexane.
[0080] The plate-shaped molded body was subjected to plasma treatment using an Openair (registered trademark) plasma treatment device (using a plasma generator FG5001 and a plasma jet nozzle RD1004, manufactured by Plasmatreat Inc.) at an irradiation speed (movement speed of the plasma jet nozzle) of 2.5 m / min and an irradiation distance of 10 mm. The frequency of the applied voltage of the power supply in the treatment device was 21 kHz. The room temperature during the plasma treatment was 23°C.
[0081] After the plasma treatment, further surface treatment was carried out using water (distilled water) as the treatment liquid. Specifically, the plate-shaped molded body was immersed in water in a container, and after 1 minute, the plate-shaped molded body was removed. It was left until it was visually confirmed that there was no water on the surface of the molded body, and a surface-modified molded body was obtained.
[0082] Then, a urethane adhesive ("WS292A" manufactured by Yokohama Rubber Co., Ltd.) was applied to the surface of the surface-modified plate-shaped molded article at room temperature (23°C) using a dedicated application gun to form a 3 mm thick adhesive layer, thereby obtaining a test specimen. The test specimen was aged for one day at room temperature and humidity. After aging, the test specimen was subjected to the above-mentioned knife cut test to evaluate adhesion. The results are shown in Table 1.
[0083] (Example 1-2) Plasma treatment was performed under the same conditions as in Example 1-1, and surface treatment was carried out. However, the subsequent treatment of adsorption of treatment liquid molecules was carried out by spraying the treatment liquid (distilled water) onto the surface of the molded body using a commercially available sprayer, rather than by immersion in water, to obtain a surface-modified molded body. Test pieces were prepared and adhesive properties were evaluated in the same manner as in Example 1-1.
[0084] (Example 1-3) Plasma treatment was performed under the same conditions as in Example 1-1, and surface treatment was performed. However, the subsequent treatment of adsorption of the treatment liquid molecules was not performed, and a surface-modified molded body was obtained. Test pieces were prepared in the same manner as in Example 1-1, and adhesion was evaluated.
[0085] (Example 1-4) Test pieces were prepared in the same manner as in Example 1-1 except that no plasma treatment was carried out, and the adhesiveness was evaluated.
[0086] The results of Examples 1-1 to 1-4 are shown in Table 1.
[0087] [Table 1]
[0088] (Example 2-1) Test pieces were prepared in the same manner as in Examples 1-1 to 1-3, except that the molded articles used were made of PBT2, and the adhesiveness was evaluated.
[0089] The results of Examples 2-1 to 2-3 are shown in Table 2.
[0090] [Table 2]
[0091] (Example 3-1 to Example 3-3) Test pieces were prepared in the same manner as in Examples 1-1 to 1-3, except that the molded body used was made of PBT3, and the adhesiveness was evaluated.
[0092] The results of Examples 3-1 to 3-3 are shown in Table 3.
[0093] [Table 3]
[0094] (Example 4-1 to Example 4-3) Test pieces were prepared in the same manner as in Examples 1-1 to 1-3, except that the molded articles used were made of PA (PA6T / 6I), and the adhesiveness was evaluated.
[0095] The results of Examples 4-1 to 4-3 are shown in Table 4.
[0096] [Table 4]
[0097] (Example 5-1 and Example 5-2) Test pieces were prepared in the same manner as in Example 1-1 and Example 1-3, except that the molded body used was made of PEI, and the adhesiveness was evaluated.
[0098] The results of Examples 5-1 and 5-2 are shown in Table 5.
[0099] [Table 5]
[0100] Tables 1 to 5 show that the CF ratio increases and adhesiveness improves when water molecules are adsorbed onto the surface after plasma treatment. The molded body made of PA6T / 6I in Table 4 had higher adhesiveness than molded bodies made of other materials even with plasma treatment alone, but it was found that adhesiveness can be further improved by performing water molecule adsorption treatment after plasma treatment.
[0101] (Example 6-1) As in Example 2-1, a molded body made of PBT2 was prepared and subjected to plasma treatment and cleaning. Then, instead of using water as the treatment liquid, acetone (Sankyo Chemical Co., Ltd., pure acetone, concentration: 99.5% or higher) was applied to the surface of the molded body by wiping with a nonwoven wiper (Bencotto). The molded body was left to stand until it was visually confirmed that no liquid was present on the surface, yielding a surface-modified molded body. As in Example 2-1, test specimens were prepared and adhesiveness was evaluated.
[0102] (Example 6-2) Test pieces were prepared in the same manner as in Example 6-1, except that the treatment liquid used was methyl ethyl ketone (MEK) (Godo Co., Ltd., for commercial use, concentration: 99% or more), and the adhesiveness was evaluated.
[0103] The results of Examples 6-1 and 6-2 are shown in Table 6.
[0104] [Table 6]
[0105] (Example 7-1) A molded body made of PBT2 was prepared in the same manner as in Example 2-1. Plasma treatment and cleaning were performed in the same manner as in Example 2-1, except that the irradiation speed was set to 10 m / min. Thereafter, instead of using water as the treatment liquid, ethanol (special grade reagent, manufactured by Amakasu Chemical Industry Co., Ltd.) was soaked in a nonwoven fabric wiper (Bencotto) and wiped onto the surface of the molded body. The molded body was left to stand until it was visually confirmed that no liquid was present on the surface, yielding a surface-modified molded body. Test specimens were prepared in the same manner as in Example 2-1, except that the curing time was set to 4 days, and adhesion was evaluated.
[0106] (Example 7-2) Test pieces were prepared in the same manner as in Example 7-1, except that butyl acetate (manufactured by WAKO Corporation, special grade reagent) was used as the treatment liquid, and the adhesiveness was evaluated.
[0107] The results of Examples 7-1 and 7-2 are shown in Table 7.
[0108] [Table 7]
[0109] From Tables 6 and 7, it was found that good adhesion of the molded body can be obtained by adsorbing molecules of a treatment liquid containing a specified organic solvent after plasma treatment.
[0110] [2. Molecular adsorption by the second form (storage under high humidity)] (Example 8-1) As in Example 1-1, a plate-shaped molded body (25 mm × 150 mm × 5 mm) made of resin PBT1 was prepared and subjected to plasma treatment and cleaning under the same conditions as in Example 1-1. Next, in this example, the molded body after plasma treatment was placed in a space under an environment of room temperature (23 ° C) and humidity 50% RH for 24 hours, and a test piece was prepared. Adhesion was evaluated in the same manner as in Example 1-1.
[0111] (Example 8-2) Test pieces were prepared in the same manner as in Example 8-1, except that they were stored in a space under an environment of 80% RH for 1 hour, and the adhesiveness was evaluated.
[0112] (Example 8-3) Test pieces were prepared in the same manner as in Example 8-1, except that they were stored in a space under an environment of 80% RH for 24 hours, and the adhesiveness was evaluated.
[0113] (Example 8-4) Test pieces were prepared in the same manner as in Example 8-1, except that they were stored in a space under an environment of 90% RH for 1 hour, and the adhesiveness was evaluated.
[0114] (Example 8-5) Test pieces were obtained in the same manner as in Example 8-1, except that they were stored in a space under an environment of 90% RH for 24 hours, and the adhesiveness was evaluated.
[0115] The results of Examples 8-1 to 8-5 are shown in Table 8 (Example 1-3 is listed again).
[0116] [Table 8]
[0117] (Example 9-1 to Example 9-5) Test specimens were prepared in the same manner as in Examples 8-1 to 8-5, except that the molded articles used were made of PBT2, and the adhesiveness was evaluated.
[0118] The results of Examples 9-1 to 9-5 are shown in Table 9 (Examples 2-3 are listed again).
[0119] [Table 9]
[0120] (Example 10-1 to Example 10-5) Test pieces were prepared in the same manner as in Examples 8-1 to 8-5, except that the molded articles used were made of PBT3, and the adhesiveness was evaluated.
[0121] The results of Examples 10-1 to 10-5 are shown in Table 10 (Example 3-3 is listed again).
[0122] [Table 10]
[0123] Tables 8 to 10 show that the adhesiveness of the examples in which the treatment solution molecules were adsorbed after the plasma treatment was improved compared to the examples in which only the plasma treatment was performed (Examples 1-3, 2-3, and 3-3). In particular, the adhesiveness was significantly improved for the samples stored at a humidity of 80% RH or higher.
[0124] This application claims priority based on Japanese Patent Application No. 2018-226297, filed with the Japan Patent Office on December 3, 2018, the entire contents of which are incorporated herein by reference. [Explanation of symbols]
[0125] 1 Vehicle structure 10 Glass (transparent substrate) 15 Shielding layer 20 Resin bracket (resin molded body) 30 Adhesive layer
Claims
1. a plasma treatment step of subjecting a molded body having a resin surface to a plasma treatment; a molecular adsorption step of adsorbing molecules of a treatment liquid containing water onto the surface of the molded body after the plasma treatment step; and a bonding step of bonding the molded body after the molecular adsorption step to a transparent substrate for a vehicle with an adhesive to obtain a vehicle structure, The molecular adsorption step is carried out by storing the molded body in a high humidity environment, In the method for manufacturing a vehicle structure, the storage in the high humidity environment is storage in an environment with a relative humidity of 80% RH or more.
2. The method according to claim 1 , wherein the treatment liquid is substantially free of an organic compound having a sulfo group.
3. The method according to claim 1 or 2, further comprising removing at least a portion of the condensed molecules of the treatment liquid after the molecular adsorption step.
4. The method according to claim 1 , wherein the resin surface of the molded body is made of a resin containing one or more of polyester, polyamide, polyacetal, polycarbonate, modified polyphenylene ether, and epoxy.
5. The manufacturing method according to claim 1 , wherein the adhesive is a moisture-curing adhesive.
6. The method according to claim 1 , wherein the transparent substrate for a vehicle is a window glass for a vehicle.
7. A method for treating a molded body for a vehicle having a resin surface that is bonded to a transparent substrate for a vehicle by an adhesive, comprising the steps of: a plasma treatment step of subjecting a molded body having a resin surface to a plasma treatment; a molecular adsorption step of adsorbing molecules of a treatment liquid containing water onto the surface of the molded body after the plasma treatment step, The molecular adsorption step is carried out by storing the molded body in a high humidity environment, The storage in a high humidity environment is storage in an environment with a relative humidity of 80% RH or more.
Citation Information
Patent Citations
JP1930-039374A
JP1932-330930A
Imparting hydrophilicity to surface of solid polymer material
JP1984215328A
Low temperature plasma treatment method
JP1987110973A
Method for storing plasma-treated article
JP1988086733A
